Status Implementasi Kebijakan Perlindungan Hukum terhadap Perempuan dan Anak dalam Kasus Kekekrasan Rumah Tangga di Lampung - Idrus Alghiffary (Bulletin of Community Engagement, 2024)
This research aims to implement legal protection policies by the Lampung Provincial Government through PERGUB Number 62 of 2021 concerning mechanisms, prevention, handling and social reintegration of victims of violence against women and children. The research method uses normative juridical law. To obtain data in this legal research, the author uses several approaches, namely the statutory approach (legislative approach), the case approach (case approach), and uses a comparative approach (comparative approach). By providing provisions that guarantee victims' rights, the Lampung Provincial Government aims to provide protection to individuals who experience domestic violence with the main aim of preventing long-term traumatic impacts for victims. In this context, the Lampung Provincial Government has implemented a legal protection policy which includes an effective mechanism for handling cases of violence as well as prevention programs to reduce the amount of violence in society, in accordance with Governor Regulation No. 62 of 2021 concerning Domestic Violence. This effort aims to involve the government and society in protecting victims, especially women and children, from violence, threats of violence, torture, or treatment that constitutes human dignity and dignity.